A little-known source about the initial stage of Mongol penetration into Crimean Gothia - Kuzenkov Pavel V.; Mogarichev Yurii М. (Поволжская археология)
Most of the sources, telling about the initial stage of Mongol penetration into the Crimean Peninsula, belong to a later time (after the 14th century). Reports relating to the 20th-40th years of the 13thcentury are unique and therefore especially valuable. Among them, was almost unnoticed the testimony of the papal ambassadors Giovanni da Pian del Carpini and Benedict of Poland, who traveled to Mongolia in 1245–1247, about the Saxons, whose country was located south of the Cuman steppe. The first author reports on the successful defense of the city of Saxons from the Mongol siege, and the second directly identifies these people with the Goths. This gives grounds to associate these reports with one of the early Mongol campaigns against the Crimean Gothic (in 1222/23 or 1238/39). In this regard, the information of the authors of the 16th century (Ogier Ghiselin de Busbecq, G. Torquatus), who compared the language of the Crimean Goths specifically with the Saxon (Low German) dialect of the German language, is of the value.